A murine pressure ulcer model for evaluating persistence and treatment of Staphylococcus aureus infection - Tavecchio, Michele; Fanni, Silvia; Wu, Xuemin; Petruk, Ganna; Puthia, Manoj; Schmidtchen, Artur (Frontiers in Medicine, 2025)
Chronic wounds, particularly pressure ulcers, pose significant healthcare challenges, especially in the elderly population. This study presents an experimental murine model of chronically infected pressure ulcers using a single cycle of magnet-induced ischemic injury combined with infection by bioluminescent Staphylococcus aureus. The model addresses previous limitations in studying pressure ulcer infection pathogenesis and evaluating treatment efficacy. By combining this model with in vivo imaging system (IVIS) technology, we achieved real-time, non-invasive monitoring of infection dynamics. This approach demonstrated persistent pressure ulcer wound infection and provided temporal and spatial data on infection status. To validate the model’s utility, we evaluated the antimicrobial efficacy of TCP-25, a synthetic host defense peptide, delivered in a topical gel formulation. Our findings highlight the potential of this model for investigating wound infection mechanisms, bacterial persistence, and therapeutic interventions. This innovative approach represents a significant advancement in pressure ulcer research, offering new opportunities for developing effective treatment strategies and improving patient outcomes.